Penentuan Konstanta PID Sistem Kendali Satelit Sumbu X, Y, dan Z Menggunakan Metode Root Locus - Muhammad Bahtiar; Mohammad Aji Saputra; Aditya Dwi Airlangga; Suraduita Mupasanta; Muhammad Mujirudin; Harry Ramza; Latifah Sarah Supian (Website, 2022)
The sattelite controller can be carried out according to the orbit direction of the x, y and z axes. This control functions by determining the value of the PID constant (Proportional, Integral and Differential) through the Root Locus Method. The purpose of this study is to determine the parameters are needed by PID in controlling the LAPAN A2 Satellite using this Root Locus method. The result of P – constant on the x-axis is 31.7692, the y-axis is 38.4987 and the z-axis is 30.6559. The I – constant generated on the x-axis is 5, the y-axis is 5 and the z-axis is 5. Likewise, the D – constant generated on the x-axis is 47.2755, the y-axis is 70.2532 and the z-axis is 43.9196. All the constant values ​​mentioned are determined based on the lowest steady state error number of 0.12% for the x-axis, 0.10% for the y-axis and 0.12% for the z-axis. The overall value is the optimum system value where the steady state error value is generated from the difference between the settling time value and the steady state value multiplied by 100% with a tolerance limit of <5%.